Results 1 to 4 of 4

Math Help - log

  1. #1
    Junior Member
    Joined
    Oct 2007
    Posts
    30

    Lightbulb log

    18. Solve the equation e^(2x) = 3

    19. Solve the equation ln (3x - 2) + ln (x - 1) = 2 ln x.
    Follow Math Help Forum on Facebook and Google+

  2. #2
    Junior Member Pinsky's Avatar
    Joined
    Jan 2008
    From
    Rijeka
    Posts
    44
    e^{2x}=3
    then you ln the whole equation. And get
    x=\frac{1}{2}\ln{3}


    ln{(3x-2)}+ln{(x-1)}=2\ln{x}
    ln{(3x-2)(x-1)}=\ln{x^2}
    (3x-2)(x-1)=x^2
    2x^2-5x+2=0
    x_1=2
    x_2=\frac{1}{2}

    you solve the quadratic equation and get results.
    Follow Math Help Forum on Facebook and Google+

  3. #3
    Forum Admin topsquark's Avatar
    Joined
    Jan 2006
    From
    Wellsville, NY
    Posts
    10,212
    Thanks
    419
    Awards
    1
    Quote Originally Posted by Pinsky View Post
    ln{(3x-2)}+ln{(x-1)}=2\ln{x}
    ln{(3x-2)(x-1)}=\ln{x^2}
    (3x-2)(x-1)=x^2
    2x^2-5x+2=0
    x_1=2
    x_2=\frac{1}{2}

    you solve the quadratic equation and get results.
    That's a nice derivation. But did you notice that x_2 = \frac{1}{2} is not a solution? It doesn't lie in the domain of the original expression.

    -Dan
    Follow Math Help Forum on Facebook and Google+

  4. #4
    Junior Member Pinsky's Avatar
    Joined
    Jan 2008
    From
    Rijeka
    Posts
    44
    See it now, tnx.
    Follow Math Help Forum on Facebook and Google+

Search Tags


/mathhelpforum @mathhelpforum